Study of correlations between CT properties of retrieved cerebral thrombi with treatment outcome of stroke patients - Viltuznik Rebeka (Sciendo, 2021)
All the patients with suspected stroke are directed to whole-brain CT scan. The purpose of this scan is to look for early features of ischemia and to rule out alternative diagnoses than stroke. In case of ischemic stroke, CT diagnostics (including CT angiography) is used mainly to locate the occlusion and its size, while the Hounsfield Units (HU) values of the thrombus causing the stroke are usually overlooked on CT scan or considered not important. The aim of this study was to demonstrate that the HU value is relevant and can help in better treatment planning.